2015
DOI: 10.1111/are.12822
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, ionoregulatory, metabolic and immune responses of Persian sturgeon,Acipenser persicus(Borodin, 1897) to stress

Abstract: The physiological ionoregulatory, metabolic and immune responses of Persian sturgeon, Acipenser persicus, to acute stress were investigated. Water levels were lowered to the fish dorsal scutes, and fish were blood-sampled before stress (pre-stress), and 0, 6, 24 and 72 h after stress. Results showed that serum cortisol rapidly increased after stress, returning to initial levels at 24 h. Serum glucose significantly increased at 6 h, declining to the pre-stress levels at 72 h. Serum triglyceride and cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 41 publications
(76 reference statements)
1
25
0
Order By: Relevance
“…The stress responses in the present study were similar to those reported by Hoseini et al (2015) in Persian sturgeons subjected to a 4 hconfinement stress. Increased circulating cortisol and glucose levels, and decrease in ACH50 and lysozyme activities and thyroid hormones' levels are common responses of fish to stresses (Brown et al, 1991;Bonga, 1997;Barton, 2002;Walpita et al, 2007;Hoseini et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The stress responses in the present study were similar to those reported by Hoseini et al (2015) in Persian sturgeons subjected to a 4 hconfinement stress. Increased circulating cortisol and glucose levels, and decrease in ACH50 and lysozyme activities and thyroid hormones' levels are common responses of fish to stresses (Brown et al, 1991;Bonga, 1997;Barton, 2002;Walpita et al, 2007;Hoseini et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Also, like mammals, it was demonstrated that stress and elevated circulating cortisol levels suppress thyroid hormones' levels in fish (Brown et al, 1991;Walpita et al, 2007). Recently, it was demonstrated that stressed Persian sturgeons have high levels of circulating cortisol accompanied with low levels of T 4 and T 3 (Hoseini et al, 2015). Also, the results suggest that the effect of exogenous tryptophan on thyroid hormones presents until 72 h post-stress, when serum cortisol levels returned to prestress level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aforementioned studies clearly show that the effects of taurine on fish are situation‐ and species‐dependent. Persian sturgeon is one of the most important species inhabitants in the Caspian Sea with great aquaculture potential (Hoseini, Tort, Abolhasani, & Rajabiesterabadi, ). Recently, the effects of taurine supplementation on a sturgeon species (Persian sturgeon [ Acipenser persicus ]) were investigated showing that taurine supplementation to plant‐based diet had adverse effects on the fish performance (Hoseini, Hosseini, Eskandari, Amirahmadi, & Sudagar, ).…”
Section: Introductionmentioning
confidence: 99%